2016
DOI: 10.1080/17429145.2016.1252068
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial antagonists and hexanal-induced systemic resistance of mango fruits against Lasiodiplodia theobromae causing stem-end rot

Abstract: Induction of defense-related enzymes, such as phenylalanine ammonia lyase (PAL), peroxidase (PO), polyphenol oxidase (PPO), superoxide dismutase (SOD) and catalase (CAT) due to bacterial antagonists viz., Pseudomonas fluorescens (Pf1) and Bacillus subtilis (EPCO16) and plant-derived lipoxygenase volatile compound hexanal, were studied in mango fruits against Lasiodiplodia theobromae causing stem-end rot disease. The results showed increased induction of all the defense-related enzymes in mango fruits 3-5 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Previous studies have used similar “bioassay” approach as a practical step in the selection of BCAs for major pathogens and pests on crops. In assays carried out in vitro as well as on the carrot roots or mango fruits, the BCAs used were found to be capable of almost complete inhibition of P. coloratum or L. theobromae , respectively (El-Tarabily et al, 1997 ; Seethapathy et al, 2016 ). Seethapathy et al ( 2016 ) have demonstrated that dual culture technique of bacterial anatogonists using Pseudomonas fluorescens (Pf1) and Bacillus subtilis (EPCO16) reduced the pathogen population in vitro ; and further strengthened the cell-wall structures of mango fruits against L. theobromae infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used similar “bioassay” approach as a practical step in the selection of BCAs for major pathogens and pests on crops. In assays carried out in vitro as well as on the carrot roots or mango fruits, the BCAs used were found to be capable of almost complete inhibition of P. coloratum or L. theobromae , respectively (El-Tarabily et al, 1997 ; Seethapathy et al, 2016 ). Seethapathy et al ( 2016 ) have demonstrated that dual culture technique of bacterial anatogonists using Pseudomonas fluorescens (Pf1) and Bacillus subtilis (EPCO16) reduced the pathogen population in vitro ; and further strengthened the cell-wall structures of mango fruits against L. theobromae infection.…”
Section: Discussionmentioning
confidence: 99%
“…In that regard, efforts toward using natural enemies native to the same environment can effectively reduce or exterminate pathogen populations (AbuQamar et al, 2017 ; Syed Ab Rahman et al, 2018 ). In vitro and field studies were previously applied against L. theobromae using species of Bacillus to control seed and seedling rot of bottle gourd (Sultana and Ghaffar, 2010 ), Trichoderma and Aspergillus to control inflorescence blight of cashew (Adeniyi et al, 2013 ), and Pseudomonas to control stem-end rot on mango fruits (Seethapathy et al, 2016 ). No information exists on potential antagonistic microorganisms that have been identified to be capable of managing mango dieback disease under greenhouse/field conditions caused by L. theobromae , as a component of an IPM strategy.…”
Section: Introductionmentioning
confidence: 99%
“…They also reported that the combined treatment induces activity of defense enzymes in 'Fuerte' avocados inoculated with Lasiodiplodia theobromae and Colletotrichum gloeosporioides. In another study, dipping treatment with combination of bacterial antagonists, Bacillus subtilis and hexanal induced systemic resistance of mango fruits against Lasiodiplodia theobromae by inducing several defense-related enzymes in mango [85].…”
Section: Plant Extractsmentioning
confidence: 98%
“…and Lasiodiplodia spp. Mango [28] Hot-water treatment with benomyl followed by a prochloraz Dothiorella dominicana Mango [104] Combined Bacillus subtilis and hexanal Lasiodiplodia theobromae Mango [85] 3.7. Combined Treatments With the emergence of various fungicide-resistant isolates, and the specificity of each fungicide on the one hand, and difficulty achieving complete protection against postharvest decay using only physical or natural control on the other, one treatment alone cannot generally provide complete protection against all postharvest diseases.…”
Section: Physical Controlmentioning
confidence: 99%
“…A total of ten isolates of C. gloeosporoides were isolated, purified by single spore isolation technique and designed as Cg1-Cg10. The pathogenicity of the isolates was tested by pin prick method (Parthasarathy et al 2016b) and used for further studies.…”
Section: Isolation Of Colletotrichum Gloeosporioides Pathogenmentioning
confidence: 99%